Sun Yat-Sen, Nanyang and the 1911 Revolution - Lee, Lai To; Lee, Hock Guan (Book collections on Project MUSE., 2011)
In view of the 100th anniversary of the 1911 Revolution and Sun Yat-sen's relations with the Nanyang communities, the Institute of Southeast Asian Studies and the Chinese Heritage Centre came together to host a two-day bilingual conference on the three-way relationships between Sun Yat-sen, Nanyang and the 1911 Revolution in October 2010 in Singapore. This volume is a collection of papers in English presented at the conference. While there are extensive research and voluminous publications on Sun Yat-sen and the 1911 Revolution, it was felt that less had been done on the Southeast Asian connec.